Improvement Of The Lattice Grid Of The 1vp Fiber Cleaner - Islombek M. Nishonov (Academia One Publishing, 2025)
This article explores the enhancement of cleaning efficiency in 1VP-type fiber cleaners used in cotton processing enterprises by replacing the traditional straight bar (colosnik) grid with a trapezoidal-shaped lattice structure. The proposed modification aims to improve the separation of fine impurities and reduce fiber entrapment, ultimately leading to increased cleaning performance and lower fiber loss. Experimental analysis and theoretical justification demonstrate that the trapezoidal configuration contributes to better airflow distribution and prevents clogging during operation. The study provides a practical solution for optimizing fiber cleaner components, ensuring higher productivity and quality in primary cotton processing
Keywords: 1VP fiber cleaner; colosnik grid; lattice structure